2002
DOI: 10.1002/1521-396x(200212)194:2<447::aid-pssa447>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Current Collapse in AlGaN/GaN HEMTs Investigated by Electrical and Optical Characterizations

Abstract: Drain current collapse in AlGaN/GaN HEMTs has been studied in detail. Applying negative gate bias stress to the device caused a serious current collapse. Spatially resolved light illumination on the device combined with the measurement of series source and drain resistances revealed that the collapse was caused by the electrons trapped at the surface states between the gate and drain electrodes. Passivation of the device surface with Si3N4 film eliminated the current collapse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
34
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 9 publications
(10 reference statements)
1
34
0
Order By: Relevance
“…Thus, they revealed that enhancement of the tunneling transport processes by the barrier thinning due to the processing-induced V N -related defect donor is the dominant mechanism associated with large leakage currents through GaN and AlGaN Schottky interfaces. 9 The current collapse effects have often been observed AlGaN/GaN HFETs under quiescent gate stress 10 or pulsemode gate stress. 11,12 The collapse is also induced by drain stress.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, they revealed that enhancement of the tunneling transport processes by the barrier thinning due to the processing-induced V N -related defect donor is the dominant mechanism associated with large leakage currents through GaN and AlGaN Schottky interfaces. 9 The current collapse effects have often been observed AlGaN/GaN HFETs under quiescent gate stress 10 or pulsemode gate stress. 11,12 The collapse is also induced by drain stress.…”
Section: Introductionmentioning
confidence: 99%
“…However, some crucial problems such as large leakage current in Schottky contacts [1][2][3][4] and drain current collapse [5,6] that are related to the AlGaN surface are not completely solved. Degradation of output power under large bias and high frequency conditions due to these is particularly serious for enhancement high-power/high-frequency performances of AlGaN/GaN HFETs [7].…”
Section: Introductionmentioning
confidence: 99%
“…Although these problems impede full-scale practical exploitation of nitride-based transistors, they are not fully solved nor understood except that these problems are due to filling and emptying of surface deep traps [5,6]. However, how such filling and emptying of states takes place have not been clarified yet.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, so-called current collapse effects not only degrade microwave output performance but also impede reliable operation of the GaN-based power devices. The current collapse phenomena have often been observed in Schottky-gate AlGaN/GaN heterostructure field-effect transistors ͑SG HFETs͒ under both gate stress [1][2][3][4][5][6] and drain stress. 2,5,7 Some models based on the electron trapping by surface states have been proposed.…”
mentioning
confidence: 99%
“…2,5,7 Some models based on the electron trapping by surface states have been proposed. 6,7 However, the mechanism for the current collapse is not clarified as yet.…”
mentioning
confidence: 99%